Análise da produção científica acerca da instrumentalidade do Serviço Social na política de saúde à luz do projeto ético-político profissional - Andrade, Mayra Hellen Vieira de (2021)
This research aimed to analyze the instrumentality of Social Work in health policy, from the selection of knowledge production from the editions of the Brazilian Congress of Social Workers-CBAS, and taking the Professional Ethical-Political Project as a parameter. The collection was carried out between December 2020 and May 2021, it was a systematic bibliographic research, of the integrative review type, added to a documental survey and the method used was dialectical historical materialism. The universe consisted of 4,485 articles, with a sample of 58 articles read in full, selected from descriptors and keywords: social service, health, instrumentality, health policy and Professional Ethical-Political Project. The chronological parameter corresponded to the years 2013, 2016 and 2019 when the CBAS was carried out. The results obtained confirmed that: the professionals showed theoretical and practical knowledge about the category project and the need to materialize it in the context of health services, recognizing the connection of its fundamentals with the principles of the Unified Health System and the Health Reform Brazilian; although tacit, there was an incidence of critical social theory in the set of productions, highlighting the importance of theoretical validation and pluralism; despite the influences of the counter-reform in education, most materialize the theory-practice relationship; the bureaucratization of services impacts work processes, but social workers reinforce the perspective of law, achieving a social image that ratifies their self-image, both related to the feasibility of law, in line with the PEPP; the profession, social and production relations are crossed by antagonisms and contradictory perspectives, but as instrumentality is a mediation that supports the totality and materializes the three dimensions of the profession, it leads to the ethical recognition of health as a matter of social justice and ratifies the principles and guidelines of the PEPP. From this it is concluded that, despite the counter-reform repercussions in health, the dominant reason for the internal organization of Social Work work is emancipatory.